Classical lyricism in Italian and North American 20th-century poetry - Piantanida, C (2013)
This thesis defines ‘classical lyricism’ as any mode of appropriation of Greek and Latin monodic lyric whereby a poet may develop a wider discourse on poetry. Assuming classical lyricism as an internal category of enquiry, my thesis investigates the presence of Sappho and Catullus as lyric archetypes in Italian and North American poetry of the 20th century. The analysis concentrates on translations and appropriations of Sappho and Catullus in four case studies: Giovanni Pascoli (1855-1912) and Salvatore Quasimodo (1901-1968) in Italy; Ezra Pound (1885-1972) and Anne Carson (b. 1950) in North America. I first trace the poetic reception of Sappho and Catullus in the oeuvres of the four authors separately. I define and evaluate the role of the respective appropriations within each author’s work and poetics. I then contextualise the four case studies within the Italian and North American literary histories. Finally, through the new outlook afforded by the comparative angle of this thesis, I uncover some of the hidden threads connecting the different types of classical lyricism transnationally. The thesis shows that the course of classical lyricism takes two opposite aesthetic directions in Italy and in North America. Moreover, despite the two aesthetic trajectories diverging, I demonstrate that the four poets’ appropriations of Sappho and Catullus share certain topical characteristics. Three out of four types of classical lyricism are defined by a preference for Sappho’s and Catullus’ lyrics which deal with marriage rituals and defloration, patterns of death and rebirth, and solar myths. They stand out as the epiphenomena of the poets’ interest in the anthropological foundations of the lyric, which is grounded in a philosophical function associated with poetry as a quest for knowledge. I therefore ultimately propose that ‘classical lyricism’ may be considered as an independent historical and interpretative category of the classical legacy.